Pengaruh Terpaan Informasi Kuliner pada Instagram @CirebonBribin Terhadap Sikap Followers Mengenai Kuliner Khas Cirebon - Abdurahman, Maman; Hidayat, Mien; Yuniati, Yenni (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2022)
The use of social media continues to increase every year, especially Instagram users who are widely used to share culinary information, pictures and videos. This study aims to determine the effect of exposure to culinary information on Instagram @CirebonBribin on followers' attitudes about Cirebon culinary specialties. Because how much influence culinary information has on the attitudes of Instagram social media users needs to be investigated more deeply so that they can provide contributions and insights for business actors and policy makers to promote their regional potential. The research method and approach used is quantitative with an explanatory survey that examines a sample of @CirebonBribin Instagram followers. The theory used is Uses and Gratifications which examines the intensity of Instagram social media use, especially culinary information from @CirebonBribin on changes in followers' attitudes about Cirebon culinary specialties. The findings of the research conducted are that there is a significant influence of curiosity, duration and frequency, the content of information consumed and individual relationships (involvement) on all elements of attitude.